FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA PADA LAPORAN TAHUNAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 – 2020 - Ali Itsnaeni, Zulfina; Dwi Ari Pertiwi (JFAS : Journal of Finance and Accounting Studies, 2026)
Finding the variables determining the degree of voluntary disclosure in the annual reports of banking companies listed on the IDX between 2018 and 2020 is the aim of this study. A total of forty-two banks were chosen using a purposive sampling technique. The data was assessed using multiple linear regression. The study discovered that firm size had no effect on voluntary disclosure at a significance threshold of 0.010, which is closer to the usual criterion of 0.05. However, listing age and foreign ownership had a substantial impact on voluntary disclosure (p = 0.000, <0.05).